Analyst Optimism and Incentives under Market Uncertainty. Issue 3 (August 2017) - Chang, Jin Woo; Choi, Hae Mi
Abstract: We examine how analysts' changing incentives driven by changes in market uncertainty affect their forecast optimism. Analysts issue more optimistically biased earnings forecasts and buy recommendations under high market uncertainty ( VIX ). The lower reputational costs and larger benefits of optimistic output explain the increased optimistic output: Analysts are less likely to be penalized for inaccuracy and can stimulate more trading activity from optimistically biased output when market uncertainty is high. We find that the likelihood of analysts' turnover decreases, while the trading volume associated with optimistic output increases, with VIX . No evidence suggests that analysts' self‐selection affects our findings on optimism and market uncertainty.